The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ece3.2784
|View full text |Cite
|
Sign up to set email alerts
|

The effect of top‐predator presence and phenotype on aquatic microbial communities

Abstract: The presence of predators can impact a variety of organisms within the ecosystem, including microorganisms. Because the effects of fish predators and their phenotypic differences on microbial communities have not received much attention, we tested how the presence/absence, genotype, and plasticity of the predatory three‐spine stickleback (Gasterosteus aculeatus) influence aquatic microbes in outdoor mesocosms. We reared lake and stream stickleback genotypes on contrasting food resources to adulthood, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 79 publications
2
5
0
Order By: Relevance
“…food chain length, community composition, seasonality), our experiment provides some of the first experimental evidence that food web structure can influence the composition of the DOC pool. If effects of predators on both primary producers and bacteria are positive, as was the case in our experiment and those of others (Shurin et al 2012, Atwood et al 2013, Saarenheimo et al 2016, Sullam et al 2017, predators could stimulate both the biological pump by increasing sedimentation (Flanagan et al 2006) and the microbial carbon pump by increasing the production and degradation of DOC. In light of anthropogenic changes to aquatic ecosystems in general, and to the abundance of predators in particular (Duffy 2003, Estes et al 2011, it seems prudent to improve our understanding about the effects of food web structure on carbon sequestration pathways.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…food chain length, community composition, seasonality), our experiment provides some of the first experimental evidence that food web structure can influence the composition of the DOC pool. If effects of predators on both primary producers and bacteria are positive, as was the case in our experiment and those of others (Shurin et al 2012, Atwood et al 2013, Saarenheimo et al 2016, Sullam et al 2017, predators could stimulate both the biological pump by increasing sedimentation (Flanagan et al 2006) and the microbial carbon pump by increasing the production and degradation of DOC. In light of anthropogenic changes to aquatic ecosystems in general, and to the abundance of predators in particular (Duffy 2003, Estes et al 2011, it seems prudent to improve our understanding about the effects of food web structure on carbon sequestration pathways.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies showed that fish can stimulate the biological carbon pump by increasing primary production (Schindler et al 1997, Atwood et al 2013 and sedimentation rates (Flanagan et al 2006), resulting in reduced emission of CO 2 from freshwater ecosystems (Schindler et al 1997, Flanagan et al 2006, Atwood et al 2013. Fish can also influence the key components of the microbial carbon pump: they can have cascading effects on the abundance and composition of bacterial communities (Shurin et al 2012, Saarenheimo et al 2016, Sullam et al 2017, and on the algal contribution to DOC (Harmon et al 2009). If effects of fish on both algal and bacterial abundance are positive, as has previously been observed in experiments in freshwater ecosystems (Shurin et al 2012, Atwood et al 2013, Saarenheimo et al 2016, Sullam et al 2017, fish could stimulate both the biological pump and the microbial carbon pump, resulting in increased carbon sequestration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms play a major role in the cycling of both organic and inorganic nutrients in all major ecosystems (Falkowski et al, 2008; Junge et al, 2006; Sullam et al, 2017; Zahran, 1999). In particular, marine microbes have been linked to global nutrient cycling with community changes affecting global balances of carbon and nitrogen (Arrigo, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we believe that other variables that are not strictly limnological or morphometric, such as biotic interactions, can also be considered in future studies involving microbiota (e.g. Charvet et al, 2014;Sullam et al, 2017) or human degradation gradients (e.g. Tolkkinen et al, 2015;Volant et al, 2016).…”
Section: Discussionmentioning
confidence: 99%